Življenjski stil in pridružene bolezni kot dejavnik tveganja za pojav rakavih obolenj - Kaučič, Nuša (Placebo, 2023)
Cancer and risk factors for the development of cancer are being intensively researched, as cancer is still one of the leading causes of death in the developed world. Lifestyle is one of the main variables we can influence to reduce our risk of developing cancer. As part of this, it is recommended to maintain a healthy body weight, give up smoking, reduce alcohol consumption, protect your skin from the sun, maintain regular physical activity and follow the guidelines for a healthy diet. Certain diseases (bacterial and viral infections, immune diseases, chronic inflammation) have also been associated with cancer, so it is important to treat them in time, as this can prevent the development of cancer.
Keywords: dejavniki tveganja; pridružene bolezni; Rak (medicina); Življenjski stil